Killing of a Pearl-Spotted Owlet (Glaucidium perlatum) by Male Red Colobus Monkeys (Procolobus tephrosceles) in a Forest Fragment Near Kibale National Park, Uganda - Goldberg, Tony L.; Gillespie, Thomas R.; Rwego, Innocent B.; Kaganzi, Clovis (Official Journal of the American Society of Primatologists, 2006)
Adult male red colobus (Procolobus tephrosceles) were observed capturing and killing an owl (Glaucidium perlatum) in the Rurama forest fragment near Kibale National Park in western Uganda. The owl was not subsequently eaten by the colobus, their conspecifics, or the other primates present during the attack. Because the incident was preceded by an agonistic encounter with a raptor, the event is best interpreted as a misdirected antipredator behavior. Although antipredator behaviors are not unknown in red colobus, this is the first such incident directed against a raptor to be documented. Am. J. Primatol. 68:1–5, 2006. © 2006 Wiley-Liss, Inc.
Keywords: antipredator behavior; red colobus; Kibale; Uganda